Sustainability and Contemporary Man-Nature Divide: Aspects of Conflict and Alienation - El-Kamel Bakari, Mohamed (Consilience, 2015)
The rise of modern capitalism, which is based largely on Enlightenment thinking and the primacy of exponential economic growth, has usually been considered the starting point of environmental degradation and the abuse of nature. Post-industrial societies, therefore, have been characterized by a disturbed environment-society relationship manifesting itself as ecological disasters as well as the prevailing instrumental view of nature under the current neoliberal capitalist paradigm of development. Using this framework, this article aims to discuss whether or not the current environment-society relationship is wholly at odds with the holistic view of nature within the sustainability discourse. Some important features of globalization, such as ‘time-space distanciation,’ rising ‘corporatism,’ and ‘global consumerism’, are also relevant to this discussion. Special emphasis is placed on the increasingly conspicuous aspects of human alienation from nature within modern societies as well as the concomitant social and cultural dislocations that the lingering Man-Nature divide has engendered. Ultimately, the potential of new initiatives to bridge this divide and promote sustainability is highlighted and research questions are thrown up for further scholarly investigation.